SISTEM REKOMENDASI JURUSAN BERBASIS WEB DENGAN MENGGUNAKAN METODE K-MEANS (STUDI KASUS : SMKN 1 JOMBANG) - Nur David , Muhammad; Setyo Permadi , Ginanjar (Inovate, 2023)
Vocational education is a part of education that prepares students to work in a specific field and enables them to perform in a particular group of occupations. Therefore, in every new academic year, every student who wishes to enroll in a vocational school (SMK) will have to choose a major during their time at the school. The usual selection process for new students in vocational schools involves considering their academic records and other criteria. In order to address this issue and take into account students' interests, the author will develop a website that incorporates a department recommendation system for new students, applying the K-means method as a means of clustering new students. This is expected to provide a solution to the school's problem and assist in guiding new students based on their interests. K-Means clustering is a non-hierarchical clustering method that groups data into clusters or groups. The data will be grouped into clusters with similar characteristics, resulting in less variation in the shapes of the grouped data.The result of this research is the creation of a department recommendation system that is useful for prospective new students to receive recommendations on the major they should pursue through the department recommendation system. This is achieved by clustering the scores obtained by the students from the questions they have answered. The system aims to facilitate prospective new students in choosing the major they will pursue. keywords : Department Recommendation System, K-Means, value.